Crossing the line : racial passing in twentieth-century U.S. literature and culture - Wald, Gayle, 1965- (Durham [N.C.] : Duke University Press, 2000)
Examines constructions of racial identity through the exploration of passing narratives including Black Like Me and forties jazz musician Mezz Mezzrow's memoir Really the Blues.
Introduction : Race, passing, and cultural representation -- Home again : racial negotiations in modernist African American passing narratives -- Mezz Mezzrow and the voluntary negro blues -- Boundaries lost and found : racial passing and cinematic representation, circa 1949 -- "I'm through with passing" : postpassing narratives in Black popular literary culture -- "A most disagreeable mirror" : reflections of white identity in Black like me -- Epilogue : Passing, "color blindness," and contemporary discourses of race and identity.
Revision of the author's thesis (Ph. D.)--Princeton University, 1995.
Includes bibliographical references (pages 227-240) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: American prose literature -- 20th century -- History and criticism; Passing (Identity) -- United States -- History -- 20th century; American prose literature -- African American authors -- History and criticism; Multiracial people in literature; Passing (Identity) in literature; African Americans in literature; Group identity in literature; Race in literature; Prose américaine -- 20e siècle -- Histoire et critique; Passing (Identité) -- États-Unis -- Histoire -- 20e siècle.; Prose américaine -- Auteurs noirs américains -- Histoire et critique; Passing (Identité) dans la littérature.; Noirs américains dans la littérature.; Identité collective dans la littérature.; Race dans la littérature.; LITERARY CRITICISM -- American -- African American; African Americans in literature; American prose literature; American prose literature -- African American authors; Group identity in literature; Passing (Identity); Passing (Identity) in literature; Race in literature; Multiracial people in literature; United States; Rassenverhoudingen; Etnisch bewustzijn; Letterkunde; 1900-1999; Criticism, interpretation, etc; History